2-(β-D-GLUKOPIRANOSILOKSI) 5-HIDROKSI ASAM BENZEN ASETAT DARI BIJI TUMBUHAN BINGKEK (Entada phaseoloides Merr) - Mubarrak, Jismi (2302-0792, 2013)
Isolation of secondary metabolite compound from seeds kernel of Bingkekplant (Entada phaseoloides Merr) by column chromatographi was carried out.Extraction by maseration method with methanol, morevert the extract waspartitioned using n-hexane and ethyl acetate.The ethyl acetate extract was then purified using column chromatography.The pure compound was white amorf (weight 78 mg) which was decomposition at2020C. The pure the was analyzed by Ultra Violet (UV), Infra Red (IR), andNuclear Magnetic Resonance (NMR) spectroscophy. Spectroscopic data werecompared with literature showed that Benzene acetic acid 2-(β-Dglukopyranosiloxy)-5-hidroxy compound.